Respuesta :

[tex]y-2=-\frac{1}{3}(x+6)\\y=-\frac{1}{3}(x+6)+2[/tex]

Simply move -2 to another side.

[tex]y=-\frac{x}{3}-2+2[/tex]

Distribute -1/3 in (x+6)

[tex]y=-\frac{x}{3}[/tex]        ---> Answer

Answer:

x + 3y = 0

Step-by-step explanation:

The equation of a line in standard form is

Ax + By = C ( A is a positive integer and B, C are integers )

Given

y - 2 = - [tex]\frac{1}{3}[/tex] (x + 6) ← distribute

y - 2 = - [tex]\frac{1}{3}[/tex] x - 2 ( add 2 to both sides )

y  = - [tex]\frac{1}{3}[/tex] x ( multiply through by 3 to clear the fraction )

3y  = -  x ( add x  to both sides )

x + 3y = 0 ← in standard form